Nonleptonic B-meson decays to next-to-next-to-leading order - Manuel Egner; Matteo Fael; Kay Schönwald; Matthias Steinhauser (Journal of High Energy Physics)
Abstract We compute next-to-next-to-leading order QCD corrections to the partonic processes b → c u ¯ d $$ c\overline{u}d $$ and b → c c ¯ s $$ c\overline{c}s $$ , which constitute the dominant decay channels in standard model predictions for B-meson lifetimes within the heavy quark expansion. We consider the contribution from the four-quark operators O 1 and O 2 in the ∆B = 1 effective Hamiltonian. The decay rates are obtained from the imaginary parts of four-loop propagator-type diagrams. We compute the corresponding master integrals using the “expand and match” approach which provides semi-analytic results for the physical charm and bottom quark masses. We show that the dependence of the decay rate on the renormalization scale is significantly reduced after including the next-to-next-to-leading order corrections. Furthermore, we compute next-to-next-to-leading order corrections to the Cabibbo-Kobayashi-Maskawa-suppressed decay channels b → u c ¯ s $$ u\overline{c}s $$ and b → u u ¯ d $$ u\overline{u}d $$ .